2020
DOI: 10.15406/mojfpt.2020.08.00244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying on the yield and chemical composition of essential oils obtained from Mentha Longifolia leaves

Abstract: The present study was carried out to evaluate the influence of the drying mode (under the sun) on the yield and composition of essential oils extracted from leaves (fresh and sun dried) of Mentha longifolia. Drying under the sun increased the concentration of essential oils isolated by hydrodistillation in a Clevenger apparatus. Twenty-three components were identified by using gas chromatography (GC) and GC coupled to mass spectrometry (GC–MS). The chemical composition was dominated by the presence of piperite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Perhaps new EO compounds might have been formed during the drying process, as a previous report has shown that the constituents of lemon peel oil increase with drying [32]. Conversely, another report has shown a marked reduction in the total qualities and quantities of EOs in the cases of sweet basil, marjoram, and oregano at ambient temperatures [33]. Therefore, it may be difficult to predict the release or retention of volatile components of EOs because of the interplay of factors such as the kind of spice used, the nature of the chemotypes in the spice, and the drying method and its duration, as well as other environmental factors and phenological parameters [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps new EO compounds might have been formed during the drying process, as a previous report has shown that the constituents of lemon peel oil increase with drying [32]. Conversely, another report has shown a marked reduction in the total qualities and quantities of EOs in the cases of sweet basil, marjoram, and oregano at ambient temperatures [33]. Therefore, it may be difficult to predict the release or retention of volatile components of EOs because of the interplay of factors such as the kind of spice used, the nature of the chemotypes in the spice, and the drying method and its duration, as well as other environmental factors and phenological parameters [34,35].…”
Section: Discussionmentioning
confidence: 99%